Pelatihan Layanan Keperawatan Spiritual Lintas Agama terhadap Pengetahuan, Keterampilan, dan Sikap Perawat di Rumah Sakit. - Hidayah, Nur; Aderus, Andi; Rauf, Syamsiah; Amal, A.Adriana (State Islamic University of Sunan Ampel, 2025)
The implementation of spiritual nursing care in hospitals has not yet been optimal. Nurses, as professional healthcare providers, must be able to understand spirituality and how spiritual beliefs affect everyone’s life. Spiritual needs are the need for meaning, purpose, and hope in life, relationships with God, religious obligations, spiritual practices, relationships with others, and relationships with nurses. This study aimed to determine the effect of interfaith spiritual care training on nurses' knowledge, attitudes, and skills in providing spiritual nursing care. The research design is quantitative, using a pre-experimental pre-posttest group design. Purposive sampling was used to select samples that met the inclusion and exclusion criteria. The Wilcoxon test results showed a value of 0.001 (p-value < 0.05), indicating a significant difference in knowledge, attitudes, and skills before and after the spiritual nursing care training. This study concludes that interfaith spiritual care training positively influences nurses' knowledge, attitudes, and skills. It contributes to the field by introducing and validating a novel, interfaith-focused training program that significantly enhances nurses’ professional competencies in providing spiritual care.